Reversible trans-to-cis photoisomerization and irreversible photocyclization reactions of a Co-coordinated stilbene derivative on chiral di-β-diketonate lanthanide complexes. Issue 4 (13th January 2023) - Hou, Ziting; Huang, Yanji; Ruan, Yushan; Xu, Han; Tan, Yu; Lin, Li-Rong; Wu, Zhen-yi
Abstract : Six lanthanide complexes constructed from β-diketonates, a stilbene derivative, a trifluoroacetate anion and a water molecule, were synthesised and characterised. Their chirality, reversible photoisomerisation and irreversible photocyclisation reactions were also studied. Abstract : Six lanthanide complexes constructed from two chiral β-diketonates (d /l -fbc = 3-heptafluorobutyry l- (+)/(−)-camphorate), the stilbene derivative ( E )- N ′, N ′-bis(pyridin-2-ylmethyl)-4-styrylbenzoyl hydrazide (L), a trifluoroacetate anion (CF3 CO2 − ), and one water molecule, namely [Ln(d /l -fbc)2 (L)(CF3 CO2 )]·H2 O (LnC57 H54 F17 N4 O8, Ln = La (1, d -fbc), La (2, l - fbc), Sm (3, d -fbc), Eu (4, d -fbc), Eu (5, l - fbc), and Tb (6, d -fbc), were synthesized and characterized by single-crystal X-ray diffraction, 1 H-NMR, elemental analysis, IR and UV-vis spectroscopy, and thermal gravimetric analysis. The photoisomerization reactions of these complexes were systematically studied by means of experimental and theoretical calculations. Crystals of complexes 1, 2, 3, and 4 were obtained and belong to the monoclinic crystal system and the C 2 chiral space group. The Λ- and Δ-diastereomers coexist in their crystals and no apparent bisignate couplets are observed in their ECD spectra. Among the complexes, the photocyclization reaction is followed by the trans -to- cis photoisomerization reaction and competes with the trans -to- cis photoisomerization, then the photocyclization reaction continues. The photocyclization reaction is irreversible in this stilbene derivative and is delayed in the lanthanide complexes. These results provide a viable strategy for the design of promising new stilbene-attached dual-functional lanthanide-based optical-switching materials.